Designing Interactive E-Modules Through Journal Writing to Enhance Mathematics Pre-Service Teachers’ Questioning Skill - Galatea, Chusnul K.; Ningtyas, Yoga D.W.K.; Diniah, Putri K. (Jurusan Matematika FMIPA Universitas Negeri Manado, 2024)
This research was driven by the lack of questioning skills among pre-service teachers. Pre-service teachers tend to lack comprehensive knowledge and skills in asking effective questions. This can be seen from their tendency to ask closed-ended questions, indicating a low quality of questioning skills. Therefore, it is necessary to develop an interactive e-module integrated with journal-writing activities to improve students' questioning skills. This study aims to develop an interactive e-module based on journal writing to improve the quality of pre-service teachers' questioning skills and to determine the quality of the e-module by considering three aspects: validity, practicality, and effectiveness. This research is a Research and Development (R&D) study using the 4D model (Define, Design, Develop, Disseminate). The average validity scores from two material experts and two media experts were 4.78 and 4.65, respectively, which fall into the very good category. Furthermore, the practicality and effectiveness of the e-module based on the results of student response questionnaires were 84% (practical) and 85% (very effective), respectively. The results of questioning skills showed an increase in the number of open-ended questions asked by students, along with a decrease in the number of closed-ended questions asked by students. Thus, the interactive e-module based on journal writing has met the criteria of being valid, practical, and effective for use in learning activities of Junior High School Mathematics Studies on the content of numbers and sets and can improve students' questioning skills.